Pengaruh Pelatihan Dan Motivasi Kerja Terhadap Kinerja Karyawan Pada PT Sigma Harapan Mandiri: The Effect of Training and Work Motivation on Employee Performance at PT Sigma Harapan Mandiri - Zuhvatul Wida; Desy Suryani (Jurnal Mnajemen | Ekonomi | Akuntansi, 2025)
Performance is the most important thing when running a company, therefore companies can do several things, such as providing training and motivation to employees. Research was studied in order to understand the impact of training and work motivation on employee performance at PT Sigma Harapan Mandiri both partially and simultaneously. The method used is causal associative with a quantitative approach and uses primary data by distributing questionnaires to employees of PT Sigma Harapan Mandiri. The population and sample for this study consisted of 50 people using saturated sampling techniques. The data obtained were analyzed using the SPSS 27.0 program using multiple linear regression techniques. The research results show that there is no positive and insignificant impact of training on employee performance as described by the calculated t score of 1.178 with a significance level of 0.245. There is a positive and significant impact of work motivation on employee performance as described by the calculated t score, namely 3,926, which has a significance level of 0.000. There is a positive and significant impact between training and work motivation on employee performance, this is indicated by a calculated F score of 16,291 with a significance score of 0.000. The R-squared score was 40.9% while the other score was 59.1% which was the result of variables that were not in this study.